Peningkatan Hasil Belajar Pendidikan Agama Islam Materi Menghormati Orang Tua melalui Metode Poster Comment pada Siswa Sekolah Dasar - Purwoko Purwoko (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: This study was motivated by low student learning outcomes in Islamic Religious Education, particularly in the topic of respecting parents, due to teacher-centered instructional practices. Objective: This study aimed to improve students’ learning outcomes in Islamic Religious Education on the topic of respecting parents through the implementation of the poster comment method. Method: This study employed a Classroom Action Research (CAR) approach conducted in three cycles, consisting of planning, action, observation, and reflection stages. The participants were seven fourth-grade students of SD Islam Al Azhar 51 Bengkulu. Data were collected through learning achievement tests, observations, and documentation. Data analysis was conducted using descriptive quantitative and qualitative techniques to examine improvements in learning outcomes and instructional processes in each cycle. Result: The findings indicated an increase in the average scores and students’ learning mastery in each cycle. In the third cycle, classical learning mastery reached 100%, indicating that all students met the minimum mastery criteria. Conclusion: The poster comment method was proven effective in improving learning outcomes in Islamic Religious Education on the topic of respecting parents in fourth-grade elementary students. Contribution: This study contributes an alternative active learning strategy that teachers can apply to enhance the quality of Islamic Religious Education in elementary schools, particularly in fostering character values through participatory and collaborative approaches.